Investigation of the effects of phthalates on in vitro thyroid models with RNA-Seq and ATAC-Seq - Nazzari, Marta; Romitti, Mírian; Hauser, Duncan; Carvalho, Daniel J.; Giselbrecht, Stefan; Moroni, Lorenzo; Costagliola, Sabine; Caiment, Florian (Frontiers in Endocrinology, 2023)
Introduction Phthalates are a class of endocrine-disrupting chemicals that have been shown to negatively correlate with thyroid hormone serum levels in humans and to cause a state of hyperactivity in the thyroid. However, their mechanism of action is not well described at the molecular level. Methods We analyzed the response of mouse thyroid organoids to the exposure to a biologically relevant dose range of the phthalates bis(2-ethylhexyl) phthalate (DEHP), di-iso-decylphthalate (DIDP), di-iso-nonylphthalate (DINP), and di-n-octylphthalate (DnOP) for 24 h and simultaneously analyzed mRNA and miRNA expression via RNA sequencing. Using the expression data, we performed differential expression and gene set enrichment analysis. We also exposed the human thyroid follicular epithelial cell line Nthy-ori 3-1 to 1 µM of DEHP or DINP for 5 days and analyzed changes in chromatin accessibility via ATAC-Seq. Results Dose-series analysis showed how the expression of several genes increased or decreased at the highest dose tested. As expected with the low dosing scheme, the compounds induced a modest response on the transcriptome, as we identified changes in only mmu-miR-143-3p after DINP treatment and very few differentially expressed genes. No effect was observed on thyroid markers. Ing5, a component of histones H3 and H4 acetylation complexes, was consistently upregulated in three out of four conditions compared to control, and we observed a partial overlap among the genes differentially expressed by the treatments. Gene set enrichment analysis showed enrichment in the treatment samples of the fatty acid metabolism pathway and in the control of pathways related to the receptor signalling and extracellular matrix organization. ATAC-Seq analysis showed a general increase in accessibility compared to the control, however we did not identify significant changes in accessibility in the identified regions. Discussion With this work, we showed that despite having only a few differentially expressed genes, diverse analysis methods could be applied to retrieve relevant information on phthalates, showing the potential of in vitro thyroid-relevant systems for the analysis of endocrine disruptors.